Maxicircle CR1 transcripts of Trypanosoma brucei are edited and developmentally regulated and encode a putative iron-sulfur protein homologous to an NADH dehydrogenase subunit. - Souza, A E (1992)
The maxicircle of Trypanosoma brucei encodes components of the mitochondrial oxidative phosphorylation system, as do other mitochondrial DNAs, but maxicircle gene identification is complicated by extensive editing of some transcripts. We found that transcripts from the CR1 region were extensively edited, as are other transcripts from maxicircle regions which exhibit strong G versus C strand bias. Editing added 259 uridines and removed 46 uridines to produce an approximately 574-nucleotide mature mRNA. Partially edited cDNAs and potential guide RNAs were also characterized. Initiation and termination codons were created, and they defined an open reading frame encoding a predicted protein of 145 amino acids. This protein contains two iron-sulfur cysteine motifs and is homologous to a subunit of NADH dehydrogenase and to other electron-carrier proteins. Higher levels of both edited and unedited CR1 transcripts accumulated in bloodstream forms of the parasite than in procyclic forms, suggesting developmental regulation of CR1 gene expression.